1999
DOI: 10.1093/qjmed/92.11.643
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CT scanning and adrenal vein sampling in the pre-operative localization of aldosterone-secreting adrenal adenomas

Abstract: In primary hyperaldosteronism, it is important to distinguish between unilateral and bilateral disease, as management strategies differ. In the period 1983-95, we identified 34 patients with primary hyperaldosteronism. Following further investigations, a diagnosis of aldosterone-secreting adenoma was made in 17 patients, and surgery was performed. Computed tomography clearly localized an apparent adenoma (discrete adenoma=1 cm diameter; normal contralateral gland) in only 10 of these patients (59%); two of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 13 publications
1
30
0
1
Order By: Relevance
“…Previous studies determined the clinical impact of adrenalectomy chosen based on CT alone or CT plus AVS (5,14,(17)(18)(19). Those authors reported that the reduction in BP, number of hypertensive medications, plasma aldosterone, and potassium normalization at follow-up were equivalent in the two groups and concluded that CT could be used to diagnose nodules >10 mm reliably and that AVS should be used when CT is normal or both adrenal glands are abnormal (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies determined the clinical impact of adrenalectomy chosen based on CT alone or CT plus AVS (5,14,(17)(18)(19). Those authors reported that the reduction in BP, number of hypertensive medications, plasma aldosterone, and potassium normalization at follow-up were equivalent in the two groups and concluded that CT could be used to diagnose nodules >10 mm reliably and that AVS should be used when CT is normal or both adrenal glands are abnormal (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, before making this decision, an affected-to-unaffected aldosterone ratio >2.2 with an unaffected-to-inferior vena cava (IVC) ratio <1.7 were used to define lateralization (18). Concordance was defined as CT showing a normal gland contralateral to the aldosterone lateralization.…”
Section: Definition Of Primary Aldosteronismmentioning
confidence: 99%
“…Both CT and MR imaging have been used for the detection of aldosterone-producing adenoma. If the imaging results are equivocal, then adrenal venous sampling, an invasive and a technically difficult procedure, is indicated for further evaluation [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the performance of CT in the detection of aldosterone-producing adenoma, with sensitivities and specificities varying from 53-100% and 33-100%, respectively [2][3][4][5][6][7][8][9][10] (Table 1). Recently, we reported a sensitivity of 70% and a specificity of 100%, respectively, for MR imaging in the detection of aldosterone-producing adenoma in primary hyperaldosteronism [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the diagnosis of PA, localization should be accurately evaluated in order to select appropriate therapeutic strategies, such as unilateral adrenalectomy and drug treatment. AVS is essential to establish the correct diagnosis of PA (18)(19)(20)(21).…”
mentioning
confidence: 99%